Patient-Specific Commissural Alignment With a Self-Expanding Transcatheter Heart Valve - Ignacio Cruz-González, MD, PhD; Pablo Antúnez-Muiños, MD; Sergio López-Tejero, MD; Lars Arnold; Keith G. Oldroyd, MD, PhD (JACC: Case Reports, 2024)
A simple and reproducible technique to achieve commissural alignment during transcatheter aortic valve replacement with the Allegra valve is described. Slight rotation of the system before system insertion is necessary. Moreover, thanks to its permaflow system (Biosensors) and its radiopaque markings, small adjustments before valve deployment can be made to reassess correct alignment.